2008
DOI: 10.1002/eji.200737444
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptidyl peptidase II is dispensable for the generation of both proteasome‐dependent and proteasome‐independent ligands of HLA‐B27 and other class I molecules

Abstract: A significant fraction of the HLA-B27-bound peptide repertoire is resistant to proteasome inhibitors. The possible implication of tripeptidyl peptidase II (TPPII) in generating this subset was analyzed by quantifying the surface re-expression of HLA-B*2705 after acid stripping in the presence of two TPPII inhibitors, butabindide and AlaAla-Phe-chloromethylketone. Neither decreased HLA-B27 re-expression under conditions in which TPPII activity was largely inhibited. This was in contrast to a significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
(66 reference statements)
4
14
0
Order By: Relevance
“…Work by two independent groups (43,44) found no difference in the overall MHC class I epitope supply when TPPII was blocked by either pharmacological or genetic ablation. Investigations regarding the proteasome-dependent epitope SIINFEKL derived from OVA also did not prove a dependency on TPPII, because siRNA-mediated inhibition did not reduce epitope presentation (44) and TPP Ϫ/Ϫ cells of a knockout mouse were even better in presenting this epitope (45).…”
Section: Discussionmentioning
confidence: 97%
“…Work by two independent groups (43,44) found no difference in the overall MHC class I epitope supply when TPPII was blocked by either pharmacological or genetic ablation. Investigations regarding the proteasome-dependent epitope SIINFEKL derived from OVA also did not prove a dependency on TPPII, because siRNA-mediated inhibition did not reduce epitope presentation (44) and TPP Ϫ/Ϫ cells of a knockout mouse were even better in presenting this epitope (45).…”
Section: Discussionmentioning
confidence: 97%
“…A "model Ag," a "model peptide precursor" (i.e., OVA), and a well-known viral epitope have been applied to study the enzymatic activity of cytosolic peptidases (11, 12, 17, 36 -38). However, the function of certain peptidases in the presentation of MHC class I Ags in in vitro and in vivo systems, as well as the model Ags used in each case, have been controversial (8,10,12,36,39,40). Rock and colleagues showed that the trimming of antigenic peptides in LAP-, BH-, or PSA-deficient mice was not reduced and that there was no significant difference in the presentation of OVA8 from N-terminally extended precursors or full-length OVA (11,12,36).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Similar to the murine findings, 16 expression of MHC class I on T and B cells was higher in the patient compared with his HLA-identical healthy heterozygous sister ( Figure 1C) and a group of 10 healthy adult controls. Pretreatment of control T cells with the TPP2 inhibitor butabindide 18,19 enhanced MHC I upregulation upon phytohemagglutinin stimulation ( Figure 1D). Finally, as described in murine cells, fibroblasts of P1 also showed increased staining with b-galactosidase indicating cellular senescence ( Figure 1E).…”
Section: Tpp2-deficient Mice and Humans Share Features Of Immune Dysrmentioning
confidence: 94%